Feeling alone in your subjectivity: Introducing the State Trait Existential Isolation Model (STEIM). (15th November 2018) - Helm, Peter J.; Greenberg, Jeff; Park, Young Chin; Pinel, Elizabeth C.
Abstract: Psychologists have devoted substantial attention to social isolation and to loneliness but only recently have psychologists begun to consider existential isolation. Existential isolation is a unique form of interpersonal isolation, related to, but distinct from loneliness and social isolation. Feeling existentially isolated is the subjective sense one is alone in one's experience, and that others cannot understand one's perspective. In the current paper, we propose a conceptual model of existential isolation and review relevant evidence. The model proposes that the experience of existential isolation can be situational, context dependent, or a trait‐like pervasive sense that others do not validate one's subjective experience. The model posits acute and chronic causes of existential isolation and consequences of the state and trait forms of it. Reactions to state existential isolation produce momentary and short‐term effects whereby an individual's sense of validation of their worldview is threatened and attempts are made to eliminate this feeling. In contrast, trait existential isolation leads to reduced identification with cultural sources of meaning and withdrawal from seeking rewarding relationships, which leads to more long‐term consequences such as chronic need depletion and deficits in well‐being. We briefly discuss potential moderators that may affect whether and when individuals experience existential isolation and possible strategies for reducing existential isolation, and recommend directions for future research.